A Review on Synthetic and Pharmacological Potential of Compounds Isolated from Garcinia mangostana Linn - Swathy Unnikrishna Pillai Saraswathy; Lekshmi Chandran Pillai Lalitha; Sherifa Rahim; Chithra Gopinath; Simimole Haleema; Sumalekshmy SarojiniAmma; Hassan Y. Aboul-Enein (Elsevier, 2022)
Background: : The extracts of Garcinia mangostana (L) pericarp contain high concentration of prenylated xanthones such as α-, β- and γ-mangostin and related molecules. These extracts possess wide range of biological properties including anticancer, anti-inflammatory, anti-proliferative, antioxidant and pro-apoptotic activities. Till date, α-, β- and γ-mangostin have been extensively studied due to its applications in nutritional supplements, herbal cosmetics and pharmaceutical preparations, but only a few attempts were being made to explore the synthetic utility of these abundantly distributed xanthones. Methods: : The data were obtained from several database such as Scopus, Pubmed and Sciencefinder. Results: : This review provides an overview of the synthesis and ethnomedicinal uses of major xanthones, including α, β, andγ-mangostin, gartanin, and tovophyllin B, isolated and identified from the pericarp of the species G. mangostana. The biological and synthetic applications of the compounds obtained after the chemical modification of core xanthone skeleton of major mangostin compounds are also presented in this review. Currently available α-mangostin containing food products, their clinical, pharmacokinetic and safety studies are described. Conclusions: : The main focus of the review is the use of naturally occurring α-, β- and γ-mangostin and their derivatives, as promising scaffolds for new drug discovery.